An Examination into the relationship between the services provided by the OPD with the dimensions of service quality (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper attempts to find out the relationship  between the services provided by the OPD with  the dimensions service quality service quality of  the OPD. In other words, the impact of perceived  quality of physical facilities, Physician services  and technology based service encounters are  being checked on the service quality where the  dimensions of SERVQUAL have been studies.A  data of 300 respondents were approached in  the various OPDs situated in NCR of India  wherein around 283 filled responses were being  used for the data analysis. The data was collected  from a well-drafted questionnaire developed  considering the tested scales.It was found that  all the hypotheses have been accepted and it  can be pointed out that the physical facilities  have a impact on the measurement of the  service quality similarly the Physicians services  also impact the service quality and further the  newly added variable namely technology based  services also has an impact on the dimensions  of service quality.
Keywords: SERVQUAL; IT-Enabled services; OPD; Perceived service quality